Technical Parameters Influencing to Cayratia trifolia Fox Grape Wine Making - N. P. Minh (Journal of Global Pharma Technology, 2019)
Cayratia trifolia is a weak herbaceous climber. Its fruit is fleshy, juicy, dark purple or black. Cayratia trifolia Linn. Is a medicinally important plants and used in the treatment of various diseases. In order to utilize this valuable fruit, objective of this study focused on major technical parameters such as sugar supplementation and yeast ratio in the primary fermentation; different clarifying agents such as gelatin, kaolin, egg white, bentonite  in the secondary fermentation. Results showed that sugar concentration and yeast ratio in the initial must were very important to the ethanol, titratable acidity and aroma in wine. Gelatin was suitable in fining step to control haze turbidity in wine. From this study, consumers had more chance to enjoy a healthy food drink orginated from natural source. Keywords: Cayratia trifolia, Wine, Yeast, Sugar, Gelatin, Ethanol, Acidity, Turbidity.